2008
DOI: 10.3892/ijmm.21.1.33
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of CCl4-induced liver cirrhosis by ribbon antisense to transforming growth factor-β1

Abstract: Abstract. Transforming growth factor-ß1 (TGF-ß1) is an important mediator of tissue fibrosis, including liver cirrhosis. Ribbon-type antisense oligonucleotide to TGF-ß1 (TGF-ß1 RiAS) was designed and combined with cationic peptide derived from the nuclear localization signal of human immunodeficiency virus-1 Tat protein for enhanced cellular uptake. When Hepa1c1c7 cells were transfected with TGF-ß1 RiAS, the level of TGF-ß1 mRNA was reduced by >70%. TGF-ß1 RiAS, mismatched RiAS, and normal saline were each inj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 36 publications
2
7
0
1
Order By: Relevance
“…Furthermore, we examined the underlying regulatory mechanism as well as the role of upregulated p-CREB-1 in liver fibrosis. It is well known that TGF-β1 is a potent cytokine which promotes the activation of HSCs and liver fibrogenesis, and is highly expressed in activated HSCs and CCl 4 -induced hepatic fibrosis (16,20,21). Herein, we explored the association between p-CREB-1 and TGF-β1 in liver fibrosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, we examined the underlying regulatory mechanism as well as the role of upregulated p-CREB-1 in liver fibrosis. It is well known that TGF-β1 is a potent cytokine which promotes the activation of HSCs and liver fibrogenesis, and is highly expressed in activated HSCs and CCl 4 -induced hepatic fibrosis (16,20,21). Herein, we explored the association between p-CREB-1 and TGF-β1 in liver fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…We then examined the regulatory mechanism responsible for the effects of p-CREB-1 in liver fibrosis. It is well known that TGF-β1 may be induced by CCl 4 and plays a crucial role in rat liver fibrogenesis (16), thus it is of interest to explore the association between p-CREB-1 and TGF-β1. Herein, we used recombinant human TGF-β1 protein (10 ng/ml) to activate the HSCs, and found that the protein expression levels of p-CREB-1 were significantly increased in the TGF-β1-treated HSCs compared with the control (p<0.01) (Fig.…”
Section: Expression Of P-creb-1 Is Induced By Exogenous Tgf-β1 Inmentioning
confidence: 99%
“…28,29 Also, TGF-beta1 ribbon-type antisense oligonucleotide effectively prevented liver fibrosis. 30 Elevated TGF-beta1 expression is one of the major features associated with non-alcoholic fatty liver disease in the MCD diet feeding model. In late disease stage, TGF-beta1 signaling contributes to stellate cell activation and (myo)fibroblast generation, the latter being responsible for ECM deposition and scar formation.…”
Section: Discussionmentioning
confidence: 99%
“…TGF-β1 knockout mice have shown reduced collagen accumulation in response to liver injury (16). Inhibition of TGF-β1 gene expression or its signaling has been shown to decrease fibrosis in experimental animal model (17,18). Therefore, in this study, we selected two potent siRNA sequences for converting into shRNA and then cloning into pSilencer 1.0 vector driven by a ubiquitous U6 promoter due to its relative ease of producing shRNA transcripts.…”
Section: Discussionmentioning
confidence: 97%